PAPARAN ROKOK, STATUS GIZI, BEBAN KERJA DAN INFEKSI ORGAN REPRODUKSI PADA WANITA DENGAN MASALAH FERTILITAS RSI SULTAN AGUNG SEMARANG - Anis Nur Halimah; Sri Winarni; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2018)
Infertility is the inability of a married couple to achieve a clinical pregnancy after having sexual intercourse 2-3 times a week within 12 months or more without using contraception. The cause of infertility originating from the female factor is around 65%, while the cause of male factors is around 20%, other conditions and the unknown is around 15%. This study aims to determine the relationship of cigarette exposure, nutritional status, workload and reproductive organ infection with the incidence of infertility in women in the fertility clinic of RSI Sultan Agung Semarang in 2018. This type of research is explanatory research using a case control study design with a retrospective study approach. The population of this study were women pus who visited the fertility clinic of RSI Sultan Agung Semarang. Number of sample cases of 15 infertile women and total control of 30 fertile women. Case samples are selected using the total population, the control sample is selected using convenience sampling. The results showed that the percentage of women in the fertility clinic at Sultan Agung Hospital was more exposed to cigarette smoke (53.3%), had normal nutritional status (42.2%), had underload workload (48.9%), and did not have reproductive organ infection (62.2%).